Respuesta :

w=98 is the correct answer. First you had to switch sides of equation, and it gave us, [tex]-3(w-89)=-27[/tex]. And than divide by -3 from both sides of equation, and it gave us, [tex]\frac{-3(w-89)}{-3}=\frac{-27}{-3}[/tex]. Simplify, and it gave us, [tex]w-89=9[/tex]. You can also add by 89 from both sides of equation, and it gave us, [tex]w-89+89=9+89[/tex]. And finally simplify, and it gave us the answer is w=98 is the correct answer. Hope this helps! And thank you for posting your question at here on brainly, and have a great day. -Charlie

Step 1: Simplify both sides of the equation.


−27=−3(w−89)


−27=(−3)(w)+(−3)(−89)          (Distribute)


−27=−3w+267


Step 2: Flip the equation.


−3w+267=−27


Step 3: Subtract 267 from both sides.


−3w+267−267=−27−267


−3w=−294


Step 4: Divide both sides by -3.

\frac{-3w}{-3}=-294

\frac{−294}{-3}

w=98